Exosomal miR-2276-5p in Plasma Is a Potential Diagnostic and Prognostic Biomarker in Glioma - Sun, Jingxian; Sun, Zhenying; Gareev, Ilgiz; Yan, Tao; Chen, Xin; Ahmad, Aamir; Zhang, Daming; Zhao, Boxian; Beylerli, Ozal; Yang, Guang; Zhao, Shiguang (Frontiers in Cell and Developmental Biology, 2021)
Introduction: Exosomal microRNAs (miRNAs) play an essential role in near and distant intercellular communication and are therefore potential diagnostic and prognostic biomarkers for various cancers. This study focused on evaluation of exosomal miR-2276-5p in plasma as a diagnostic and prognostic biomarker for glioma. Methods: Plasma exosomes from 124 patients with glioma and 36 non-tumor controls were collected and subjected to quantitative real-time polymerase chain reaction (qRT-PCR) analyses for the exosomal miR-2276-5p expression. Bioinformatic analyses were performed to identify a gene target and CGGA and TCGA databases were checked for evaluation of prognostic relevance. Results: The exosomal miR-2276-5p in glioma patients had a significantly decreased expression, compared to non-glioma patients (p<0.01). ROC curve analyses were observed to regulate the diagnostic sensitivity and specificity of miR-2276-5p in glioma; the AUC for miR-2276-5p was 0.8107. The lower expression of exosomal miR-2276-5p in patients with glioma correlated with poorer survival rates. Rab 13 was identified as the target of miR-2276-5p which was high in glioma patients, especially those with higher tumor grades and correlated with poor survival. Conclusion: The circulating exosomal miR-2276-5p is significantly reduced in the plasma of glioma patients and, thus, it could be a potential biomarker for patients with glioma for diagnostic and/or prognostic purposes.